Electrical resistivity imaging in transmission between surface and underground tunnel for fault characterization - Lesparre, Nolwenn; Grychtol, Bartłomiej (Journal of applied geophysics, 2016)
Electrical resistivity images supply information on sub-surface structures and are classically performed to characterize faults geometry. Here we use the presence of a tunnel intersecting a regional fault to inject electrical currents between surface and the tunnel to improve the image resolution at depth. We apply an original methodology for defining the inversion parametrization based on pilot points to better deal with the heterogeneous sounding of the medium. An increased region of high spatial resolution is shown by analysis of point spread functions as well as inversion of synthetics. Such evaluations highlight the advantages of using transmission measurements by transferring a few electrodes from the main profile to increase the sounding depth. Based on the resulting image we propose a revised structure for the medium surrounding the Cernon fault supported by geological observations and muon flux measurements.